A porphyrin copper ion covalent organic framework material with excellent biocompatibility
By gathering the new type of bronze-pyrodia boric acid matched with 5,10,15,20-four (3,4-dihydroxylphenyl) pyrodoline, prepare a CU-COF with excellent biocompatibility and degradable CU-COF Materials solve the problem of insufficient biocompatibility and degradation in the existing technology, and realize the high -efficiency antibacterial and rapid metabolic excretion in the body.
Patent Information
- Application Number
- CN202411631629.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-15
AI Technical Summary
In the prior art, the biocompatibility and degradability of the covalent organic framework materials of the porphyrin copper ionic covalent organic framework materials are insufficient, resulting in slow metabolism and excretion in the body and limited antibacterial effect.
By gathered with 5,10,15,20-four (3,4-dihydroxylphenyl) pyrodinoline, the new type of bronze pest alkaline boric acid co-concentrated. Polymerization, forming a covalent frame material with a pyrine with excellent biocompatibility and degradability.
CU-COF slowly degrades in an acidic environment, improves the micro-environment infection, improves antibacterial effects, shortens the metabolic time in the body, and enhances biocompatibility.
Smart Images

Figure CN119143999B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedicine, and in particular to a porphyrin copper ion covalent organic framework material with excellent biocompatibility. Background Art
[0002] At present, the new antibacterial modes mainly include photothermal therapy (PTT), photodynamic therapy (PDT) and Fenton. Photothermal therapy (PTT) is a treatment method that uses materials with high photothermal conversion efficiency, injects them into the human body, gathers near the tissue using targeted recognition technology, and converts light energy into heat energy under the irradiation of an external light source to kill bacteria. PTT usually uses photothermal agents to trigger local hyperthermia under near-infrared light (NIR) irradiation. Due to the denaturation of heat shock proteins, ordinary bacteria will be killed at temperatures above 45°C. Polymer covalent organic binding materials have been proven to have certain antibacterial activity. They can interact with bacterial lipids and protein membranes through electrostatic bonds (with high negative charges), hydrogen bonds, and their van der Waals forces and π-π stacking interactions, capture bacterial cells and wrap and separate them. In addition, physical damage to bacterial cells by the sharp edges of polymer materials can cause bacterial cell membranes to rupture. Photodynamic antimicrobial therapy (PDAT) is considered to be one of the most powerful weapons against bacterial infections. PDT therapy uses photosensitizers to produce reactive oxygen species (ROS) under near-infrared light to exert therapeutic effects. After absorbing light, photosensitizers produce singlet oxygen and other reactive oxygen species through photosensitization. Photosensitizers are excited from their ground state to an excited state and converted into highly active substances (such as NO, O2, etc.), which can be used to destroy bacterial growth. Studies have found that the drug resistance of multidrug-resistant bacteria is mostly due to the formation of bacterial biofilms. Biofilms are mixtures of bacterial cells that irreversibly adhere to the surface of materials or tissues and are encapsulated in self-generated extracellular polymers. Extracellular polymers have important physiological functions, leading to hypoxia, anaerobic glycolysis, hypoxia, and ion channel disorders in the biofilm microenvironment.
[0003] Novel copper Schiff base complexes are called privileged ligands in organic chemistry. Due to their chelating properties and the ability to coordinate with various oxidized transition metal ions, novel copper Schiff base complexes are considered to be an important class of organic compounds with good anti-cancer, viral, fungal and bacterial effects, and can be used to treat diabetes, chemotherapy-resistant cases and malarial infections. Novel copper Schiff base complexes have broad application prospects not only in the field of therapy / medicine but also in industrial applications. Porphyrin is a class of macromolecular heterocyclic compounds formed by the α-carbon atoms of four pyrrole subunits interconnected by a methine bridge (=CH-). The porphyrin ring has 26 π electrons and is a highly conjugated system, which gives it a dark color. At the same time, porphyrin has certain photosensitivity. Under the action of ultraviolet or visible light, it can effectively release singlet oxygen and can effectively kill bacteria in combination. Since the new copper Schiff base complex contains metallic copper, even after combining with porphyrin, the cell hemolysis of the COF material is lower than the 5% specified by the international safety and quality standards, but it is still around 3%, and the biocompatibility needs to be improved. In addition, the COF material formed by the combination of the new copper Schiff base complex and porphyrin is difficult to degrade, making its degradation and metabolism in the body slow. Therefore, a degradable porphyrin copper ion COF material with excellent biocompatibility is needed. Summary of the invention
[0004] In view of the above-mentioned prior art, the object of the present invention is to provide a porphyrin copper ion covalent organic framework material with excellent biocompatibility. The present invention copolymerizes a novel copper Schiff base complex and 5,10,15,20-tetrakis (3,4-dihydroxyphenyl) porphyrin to obtain Cu-COF with negligible biological toxicity, and the material realizes the synergistic effect of three antibacterial modes of PDT, PTT and hydroxyl free radicals. Cu-COF can also be slowly degraded in an acidic environment, improving the infection microenvironment and enhancing the antibacterial effect during the degradation process.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a porphyrin copper ion covalent organic framework material with excellent biocompatibility. The porphyrin copper ion covalent organic framework material (Cu-COF) is obtained by solvothermal copolymerization of a porphyrin compound and a novel copper Schiff base boric acid complex under a protective atmosphere.
[0007] Preferably, the porphyrin compound is 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin.
[0008] Preferably, the preparation method of the 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin is:
[0009] (1) 3,4-dimethoxybenzaldehyde and propionic acid are mixed, and then pyrrole is slowly added dropwise, and the mixture is heated for reaction. After the reaction is completed, the propionic acid is removed under reduced pressure, and the mixture is filtered and washed in sequence. A purple powder is obtained by purification by silica gel column chromatography, namely 5,10,15,20-tetrakis(3,4-dimethoxyphenyl)porphyrin;
[0010] (2) Dissolve 5,10,15,20-tetrakis(3,4-dimethoxyphenyl)porphyrin in dichloromethane, then slowly add a mixed solution of boron tribromide and dichloromethane, react at low temperature, and naturally warm to room temperature after the reaction is completed. Add water to terminate the reaction, and after purification, obtain an olive green product, namely 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin.
[0011] Preferably, the structural formula of the novel copper Schiff base boric acid complex is
[0012] .
[0013] Preferably, the novel copper Schiff base boric acid complex is prepared by the following method:
[0014] (1) 3-Aminophenylboronic acid and methanol are mixed evenly, salicylaldehyde is added, stirred for reaction, and then filtered, washed, and dried in sequence to obtain a bright yellow product;
[0015] (2) The bright yellow product obtained in step (1) is dissolved in methanol, anhydrous copper acetate is dissolved in distilled water, the two solutions are mixed and stirred for reaction, and then filtered and washed to obtain a brown-yellow product, i.e., a novel copper Schiff base boric acid complex.
[0016] Preferably, the solvent used in the solvothermal reaction is a mixture of acetonitrile, 1,4-dioxane and mesitylene; the volume ratio of acetonitrile, 1,4-dioxane and mesitylene is 20:4:1.
[0017] Preferably, the molar ratio of the porphyrin compound to the novel copper Schiff base boric acid complex is 1:2.
[0018] Preferably, the protective atmosphere is nitrogen; the temperature of the solvent thermal reaction is 90° C. and the time is 18 h.
[0019] The second aspect of the present invention provides the use of porphyrin copper ion covalent organic framework materials in the preparation of antibacterial drugs with excellent biocompatibility or the preparation of degradable antibacterial drugs.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention has developed a new type of metallized covalent organic-bound antibacterial agent (Cu-COF) with negligible biological toxicity for "three-in-one" synergistic antibacterial treatment. Covalent organic framework (COF) is an artificial multifunctional porous material with components similar to biological macromolecules. The copolymer is obtained by solvothermal copolymerization of porphyrin compounds and new copper Schiff base boric acid complexes under a protective atmosphere to obtain Cu-COF containing metal copper ions. The insertion of the metal center makes Cu-COF have POD-like enzyme activity, which can convert endogenous H2O2 in the infection microenvironment into toxic ·OH. The Cu-COF prepared by the present invention has three antibacterial modes of PDT, PTT and hydroxyl radicals, and three-in-one synergistic antibacterial ability.
[0022] (2) The Cu-COF of the present invention can kill Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus to a large extent in vitro, and can be used as a new antibacterial material. At the same time, it also has a good healing effect on bacterial infection wounds on the back of mice. Cu-COF can also be slowly degraded in an acidic environment, improving the infection microenvironment and antibacterial effect during the degradation process, and shortening the metabolic time of Cu-COF in the body.
[0023] (3) The Cu-COF of the present invention acts on the diseased cells, generates reactive oxygen species under near-infrared light, improves the intracellular hypoxic microenvironment, and thus exerts a therapeutic effect. After absorbing light, the material generates singlet oxygen and other reactive oxygen species through photosensitization, thereby killing cells. Under red light (e.g., 638 nm) irradiation, it can cooperate with photodynamic and photothermal therapy. In a weak acid environment, it can also convert low-concentration hydrogen peroxide into hydroxyl free radicals, and the Fenton synergistic bactericidal treatment effect is significantly enhanced, which has potential application value in biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 :(a)Low-temperature N2 absorption isotherm;(b)Pore size distribution curve of Cu-COF;(c)Thermogravimetric analysis of Cu-COF;(d)XRD spectrum of Cu-COF;(e)Infrared spectrum of Cu-COF;
[0025] Figure 2:(a) TEM of Cu-COF with a scale of 500 nm;(b) TEM of Cu-COF with a scale of 200 nm;(c) TEM of Cu-COF with a scale of 50 nm;(d) HR-TEM of Cu-COF with a scale of 10 nm;(e) HR-TEM of Cu-COF with a scale of 5 nm;(f) HR-TEM of Cu-COF with a scale of 5 nm;(g) SEM of Cu-COF with a scale of 10 μm;(h) SEM of Cu-COF with a scale of 500 nm;(i) SEM of Cu-COF with a scale of 200 nm;
[0026] Figure 3 :(a)HADDF-STEM image of Cu-COF, scale bar 200 nm;(b)C element distribution map of Cu-COF;(c)O element distribution map of Cu-COF;(d)N element distribution map of Cu-COF;(e)B element distribution map of Cu-COF;(f)Cu element distribution map of Cu-COF;
[0027] Figure 4 :(a) Temperature curves of Cu-COF at different concentrations;(b) Cu-COF aqueous solution (125 μg / mL) under five laser beams (λ = 638 nm, 1.2 W / cm 2 ) Temperature variation curve of the on / off cycle of irradiation; (c) Photothermal curve of Cu-COF at different power densities; (d) Cu-COF aqueous solution (125 μg / mL) under a single laser (λ = 638 nm, 1.2 W / cm 2 ) Temperature change curve of irradiation on / off cycle; (e) Relationship between temperature change difference and concentration of Cu-COF; (f) Relationship between temperature change difference and power density of Cu-COF; (g) Corresponding infrared thermal imaging of water and Cu-COF; (h) Relationship between cooling time and negative natural logarithm of temperature;
[0028] Figure 5 :(a) UV-visible spectrum of DPBF under laser irradiation;(b) UV-visible spectrum of Cu-COF + DPBF under laser irradiation;
[0029] Figure 6:(a) UV-visible absorption spectra of Cu-COF solutions at different pH values;(b) UV-visible absorption spectra of Cu-COF solutions at different concentrations;(c) UV-visible spectra of four different groups (TMB + H2O2, H2O2+Cu-COF, TMB +Cu-COF, TMB + H2O2+Cu-COF);(d) Effect of 638 nm laser irradiation (1.2 W / cm 2) on the peroxidase-like catalytic activity of Cu-COF (125 μg / mL).
[0030] Figure 7 :(a)Photos of bacterial colonies formed by Staphylococcus aureus after being treated by each group;(b)Photos of bacterial colonies formed by Escherichia coli after being treated by each group;(c)Bacterial survival rate of Staphylococcus aureus after being treated by each group;(d)Bacterial survival rate of Escherichia coli after being treated by each group;
[0031] Figure 8 :(a) Fluorescence images of Staphylococcus aureus after various treatments and co-staining;(b) Fluorescence images of Escherichia coli after various treatments and co-staining;
[0032] Fig. 9 :(a)TEM images of Staphylococcus aureus after co-staining with various treatments;(b)TEM images of Escherichia coli after co-staining with various treatments;
[0033] Fig.10 :(a)Hemolysis diagram of Cu-COF at different concentrations;(b)MTT assay of 3T3 after treatment with different concentrations for 24 h;(c)Cell migration assay through wound healing;
[0034] Fig.11 : Photos of back wounds of mice infected with Staphylococcus aureus after treatment in each group;
[0035] Fig.12 :(a)Wound area and time change curve;(b)Changes in mouse body weight during treatment;
[0036] Fig.13 : H&E and Masson staining images of wound tissues in each group on the 11th day of wound healing;
[0037] Fig.14 : H&E staining of the main organs of mice in different treatment groups: heart, liver, spleen, lung and kidney;
[0038] Fig.15 :Absorbance variation of Cu-COF at different pH and time;
[0039] Fig.16: Synthesis route of Cu-COF. DETAILED DESCRIPTION
[0040] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0041] As described in the background technology section, metal-containing porphyrin-based antibacterial drugs have poor biocompatibility. Based on this, the purpose of the present invention is to provide a porphyrin copper ion covalent organic framework material with excellent biocompatibility. The present invention first prepares octahydroxyporphyrin and a novel copper Schiff base boric acid complex, both of which contain hydroxyl groups, and dehydrates the hydroxyl groups of the two to form a borate structure, so that the octahydroxyporphyrin and the novel copper Schiff base boric acid complex are polymerized to obtain Cu-COF with negligible biological toxicity. Cu-COF combines the good fungal and bacterial effects of the novel copper Schiff base boric acid and the photosensitivity and metal ion recognition characteristics of 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin, realizes the three-in-one combined antibacterial of PDT, PTT and hydroxyl free radicals, and has potential application value in the field of medicine. The borate bond in Cu-COF will slowly break in an acidic environment, allowing Cu-COF to slowly degrade in the body and then be metabolized and excreted. After entering the human body, it will consume acid and slowly degrade within a few days. At the same time, the consumption of acid will improve the infection microenvironment and promote the growth of normal cells. Therefore, Cu-COF not only achieves degradation, but also improves the infection microenvironment and improves the antibacterial effect during the degradation process.
[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0043] Description: Anhydrous copper (II) acetate was purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd. with a CAS number of 147-71-2.
[0044] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0045] Example 1: Preparation of Cu-COF
[0046] (1) Preparation of 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin:
[0047] (a) 3,4-dimethoxybenzaldehyde (42 mmol, 6.98 g) and pyrrole (43 mmol, 3.00 g) were refluxed in propionic acid at 150°C for 4 h, and then the propionic acid was removed under reduced pressure. The product was filtered and washed with methanol until the filtrate was colorless. Purification by silica gel (dichloromethane / n-hexane volume ratio = 5 / 1) column chromatography gave a purple powder, namely 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin, named 3,4-TDMPP. The synthesis route is as follows:
[0048] .
[0049] (b) First, dissolve boron tribromide (12 mmol, 1.14 mL) in 12 mL of dichloromethane to obtain a 1 mol / L boron tribromide solution. Dissolve 3,4-TDMPP (1 mmol, 0.855 g) in 20 mL of dichloromethane to obtain a 3,4-TDMPP solution. In a nitrogen atmosphere at -78°C, add the boron tribromide solution to the 3,4-TDMPP solution with a syringe, react at -78°C for 24 hours, and after the reaction temperature naturally rises to room temperature, add 50 mL of distilled water to terminate the reaction. Filter with a Buchner funnel, collect the filter residue and dry it under vacuum to obtain an olive green product, namely 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin, named 3,4-TDHPP. The synthetic route is as follows:
[0050] .
[0051] (2) Synthesis of novel copper Schiff base borate complex (Cu-B)
[0052] (a) 3-Aminophenylboronic acid (2.87 g, 21 mmol), salicylaldehyde (2.56 g, 21 mmol) and 50 mL of methanol were added to a 100 mL beaker and stirred at room temperature with a magnetic stirrer for 90 min. After the reaction was completed, the product was filtered under reduced pressure. The product was washed with a small amount of cold water and methanol and dried in vacuo to obtain a bright yellow product. The synthetic route is as follows:
[0053] .
[0054] (b) The bright yellow product (0.54 g, 2.26 mmol) obtained in step (a) was dissolved in 15 mL of methanol; anhydrous copper (II) acetate (0.2256 g, 1.13 mmol) was dissolved in 5 mL of distilled water. The two solutions were mixed and stirred at room temperature for 5 days. After the reaction, the precipitated complex was separated, washed with methanol and water in turn, and dried under vacuum to obtain a new copper Schiff base boric acid complex, named Cu-B. The synthesis route is as follows:
[0055] .
[0056] (3) Preparation of Cu-COF:
[0057] Acetonitrile: 1,4-dioxane: mesitylene were mixed in a volume ratio of 20:4:1 to obtain a mixed solvent. 3,4-TDHPP (742.21 mg, 1 mmoL) and Schiff base copper borate complex Cu-B (1.084 g, 2 mmoL) were added to 75 mL of the mixed solvent and reacted at 90 °C for 18 h under N2 protection. After the reaction was completed, it was cooled to room temperature and directly filtered. The filtrate was washed with ethanol / methanol, DMF, DMSO, THF, and dichloromethane in turn until the filtrate was colorless, and then dried in a vacuum drying oven at 50 °C to obtain Cu-COF. Synthesis route see Fig.16 .
[0058] Example 2: Characterization
[0059] (1) The porosity of Cu-COF was estimated by low-temperature N2 adsorption-desorption experiments. Figure 1 As shown in (a), Cu-COF exhibits a typical type-iv isotherm with strong gas absorption at low pressure (P / P0 < 0.01), followed by a large hysteresis, indicating the coexistence of micropores and mesopores in Cu-COF.
[0060] The pore size distribution curve can also intuitively reflect the pore characteristics of Cu-COF. Figure 1 As shown in (b), the pore size distribution of Cu-COF ranges from 4.19 to 45 nm, and has multiple peaks, which further verifies the hierarchical pore structure of Cu-COF.
[0061] In a nitrogen atmosphere, as the temperature increases, Figure 1 (c) The weight of Cu-COF decreases dramatically and still maintains 47% of its initial weight value at 800 °C.
[0062] The crystalline properties of Cu-COF were verified by X-ray diffraction (XRD) analysis, such as Figure 1 As shown in (d), the presence of obvious diffraction peaks proves that Cu-COF has a certain degree of crystallinity.
[0063] The structure of Cu-COF was analyzed by infrared spectroscopy. The FTIR of Cu-COF combines the characteristics of 3,4-TDHPP and Cu-B, such as Figure 1As shown in (e), in the FTIR of 3,4-TDHPP, a broad and strong hydroxyl characteristic absorption peak is shown in the range of 3000-3600 cm-1, the stretching vibration of C=C is observed at 1518 cm-1, the stretching vibration of C=N is observed at 1608 cm-1, there is a broader absorption peak caused by the stretching vibration of NH on the porphyrin ring at 3200 cm-1~3400 cm-1, and some characteristic porphyrin absorption bands are observed in the range of 400-1750 cm-1; in the FTIR of Cu-B, the stretching vibration of C=N is observed at 1628 cm-1, and a broader hydroxyl characteristic absorption peak in the boric acid structure is also shown in the range of 3000-3600 cm-1, and an absorption peak of Ar-O is shown at 1225 cm-1; while in the FTIR of Cu-COF, the hydroxyl characteristic absorption peak disappears, and at 1310 The stretching vibration of BO was observed at cm-1, and the broader absorption peak caused by the stretching vibration of NH on the porphyrin ring still existed, and other characteristic peaks were retained, indicating that the synthesis of Cu-COF was successful.
[0064] (2) The surface morphology of the synthesized Cu-COF was studied using field emission scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 2 As shown, Cu-COF is mainly composed of interconnected irregular blocks, and there are a large number of intertwined pores throughout the polymer matrix. The TEM results clearly show that the surface rough Cu-COF is formed by a multilayer block structure. It can be seen that Cu-COF is an ordered structure, and local stripes with cyclic marks appear on the edge. It can also be intuitively observed from high-angle annular dark field scanning TEM (HAADF-STEM) that Cu-COF has a layered structure with interconnected macropores. At the same time, Figure 3 The EDS elemental mapping further reveals that the porous polymer is dominated by carbon and that N, O, B, and Cu are uniformly distributed in Cu-COF.
[0065] Example 3: Performance Test
[0066] (1) Photothermal conversion performance test
[0067] Cu-COF aqueous suspensions of different concentrations (0, 50, 100, 125, 150, 175, and 200 μg / mL) were prepared in distilled water and added to 1.5 mL EP tubes. PBS was used as a blank control. Then, a 638 nm near-infrared laser (power density of 1.2 W / cm 2 ) for 10 min. The temperature value was displayed on the thermal imaging display, and the temperature rise within 10 min was taken every 40 s for plotting. In addition, 0.6, 1.2 and 1.8 W / cm2 The 638 nm near-infrared laser was used to irradiate a 125 μg / mL Cu-COF suspension for 10 min. The samples were taken every 40 s for mapping. The temperature change during irradiation was monitored using an infrared thermal imager, and the temperature images of the sample suspension at different times were taken. The photothermal stability of Cu-COF was then evaluated by heating / cooling (ON / OFF) cycle irradiation experiments. 2 1 mL of Cu-COF suspension (125 μg / mL) was irradiated with a 638 nm near-infrared laser. The laser was turned off after 10 minutes of irradiation. The laser was turned on again after the water suspension stabilized to room temperature. The laser was turned on / off five times, and the heating and cooling process of the Cu-COF water suspension was recorded for five cycles. The temperature changes were recorded throughout the experiment. One of the cycles was taken out separately for plotting, and the photothermal conversion efficiency was calculated by the temperature change during the cooling process.
[0068] The photoresponsivity of Cu-COF was studied by changing the sample concentration or adjusting the laser power density. In order to prove that COF has good photothermal conversion performance, the photoresponsivity of Cu-COF with different concentrations (50-200 μg / ml) was first detected under laser irradiation (λ=638 nm, 1.2 W / cm 2 , 10 min). Figure 4 As shown in (a), Cu-COF has a concentration-dependent photothermal conversion capability, and its temperature increases significantly with the concentration of Cu-COF. For example, when the concentration is 50 μg / mL, the temperature rise (ΔT) of the Cu-COF material is the lowest, at 12.3°C. As the concentration increases, the ΔT of the solution increases significantly, reaching a maximum value of 28.9°C at 200 μg / mL; Figure 4 (g) The temperature image obtained by the thermal imager also intuitively reflects this concentration-related temperature rise behavior. Under the same conditions, the temperature of pure water hardly changes. Figure 4 (c) shows that the photothermal conversion ability of Cu-COF increases with the increase of laser power. When the Cu-COF drug concentration is 125 μg / mL, the photothermal conversion ability of Cu-COF increases with the increase of laser power. 2 The laser power density of 1.2 W / cm 2 It can increase the temperature of Cu-COF from 23.6℃ to 47.5℃. Figure 4 (e) shows the difference in temperature change of Cu-COF at different concentrations. As the concentration increases, the temperature difference of Cu-COF gradually decreases. Figure 4(f) shows the temperature change difference of Cu-COF under different laser powers. It can be seen from the figure that with the increase of laser power, the temperature difference of Cu-COF gradually tends to be flat and reaches a certain peak value. In addition, photothermal stability is an important factor in the practical application of phototherapy. In order to study the photothermal conversion stability of Cu-COF, Figure 4 (b) The 638 nm wavelength (1.2 W / cm 2 ) The laser light source was switched on and off five times to observe the photothermal conversion of Cu-COF. It can be clearly observed that Cu-COF is relatively stable and the temperature rise and fall process almost overlaps, which is very necessary in practical applications. This shows that the prepared Cu-COF has good photothermal stability and can be used as a potential photothermal antibacterial agent.
[0069] Photothermal conversion efficiency of Cu-COF: η (%) = 64.9%. The photothermal conversion efficiency calculation formula is calculated by referring to the photothermal conversion efficiency formula in "A Photothermal-Fenton-like Reaction Artificial Nanozyme and Its Preparation Method and Application" disclosed in application number CN202310175497.X. Figure 4 (d) is the temperature rise and fall process of a single laser switch, which is used to calculate the photothermal conversion efficiency of Cu-COF. Figure 4 (h) shows the τS and θ values in the photothermal conversion efficiency calculation formula.
[0070] (2) By detecting singlet oxygen in Cu-COF ( 1 O2) generation to evaluate its photodynamic performance.
[0071] 1,3-Diphenylisobenzofuran (DPBF) is a singlet oxygen ( 1 O2) specific capture agent to detect singlet oxygen generated by Cu-COF. 1 When O2 comes into contact with the DPBF, it will destroy the π electron system in the DPBF, causing it to lose its characteristic spectral absorption, resulting in a decrease in absorbance. First, prepare the DPBF probe solution (dissolve 30 μL of DPBF in 3 mL of DMF solution) and adjust its absorbance to around 1.0. Use a 638 nm laser (1.2 W / cm 2 ) for 0, 2, 4, 6, 8, and 10 min, and the UV absorption was measured to prove the stability of the DPBF probe. Subsequently, a Cu-COF (200 μg / mL) DMF solution was prepared and 30 μL of DPBF probe was added. After mixing evenly, the probe was illuminated at a wavelength of 638 nm (1.2 W / cm 2) red light was irradiated into the cuvette for different times, and the absorption spectrum was immediately measured using a UV spectrophotometer. In addition, the amount of singlet oxygen generated was calculated by subtracting the absorbance of the material itself. Each set of experiments was repeated three times. The UV absorption after irradiation was detected, and the Cu-COF UV absorption was plotted.
[0072] Figure 5 (a) shows the natural decay of pure DPBF after 638 nm laser irradiation for different time periods, and only a small decay rate is detected. As shown in Figure 5 (b), Cu-COF can induce the production of toxic ROS ( 1 O2), which is irradiated by laser (638 nm, 1.2 W / cm 2 ) It can be verified that the characteristic absorption intensity of DPBF around 425 nm gradually decreases within 10 min.
[0073] (3) Hydroxyl radical generation ability test
[0074] A Cu-COF solution with a concentration of 125 μg / mL was prepared and made up to 1 mL with PBS at pH 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5, and its UV absorption was detected under a UV spectrophotometer. A total volume of 1 mL was prepared with Cu-COF solutions (prepared with PBS) at concentrations of 0, 50, 100, 125, 150 and 200 μg / mL, respectively. The pH of the Cu-COF solution was 4.5, and its UV absorption at different concentrations under the same pH conditions was detected. Four solutions of H2O2+ TMB, H2O2+Cu-COF, TMB+Cu-COF and TMB +H2O2+Cu-COF were prepared. The concentration of TMB in the four solutions was 200 μl / mL, the concentration of H2O2 was 100 μl / mL, and the concentration of Cu-COF was 125 μg / mL. The total volume of each solution was 1 mL, and it was made up with PBS with a pH of 4.5, and its ultraviolet absorption was detected. Afterwards, in order to verify whether light affects the enzyme activity of Cu-COF, a 125 μg / mL MC-COF-I aqueous solution was prepared, and its ultraviolet absorption was detected before and after illumination and plotted.
[0075] like Figure 6 As shown in (a), the enzyme activity of Cu-COF is strongly related to the pH of the solution. As the pH decreases from 6.5 to 1.5, the enzyme activity first increases and then decreases, reaching a maximum at pH 3.5. Figure 6 As shown in (b), with the increase of Cu-COF concentration, the generation of ·OH by the system is significantly enhanced, which can also be confirmed by the increase of UV absorption at 650 nm. This result shows that the enzyme activity of Cu-COF is concentration-dependent. Figure 6(c)Observed, the groups of Cu-COF + H2O2 and Cu-COF + TMB do not produce visible blue changes or detectable UV-vis absorption at 650 nm. In contrast, even in the presence of H2O2 and TMB, the Cu-COF solution does not produce blue color or absorption at 650 nm. This indicates that the peroxidase-like catalytic activity of Cu-COF is attributed to the presence of the novel copper Schiff base borate complex. Considering the weakly acidic physiological environment after bacterial infection, the enzyme activity of Cu-COF at a concentration of 125 μg / mL in the weakly acidic state (5.5 < pH < 6.5) was selected. From Figure 6 (d)It can be clearly seen that the UV absorption intensity (λ = 650 nm) collected under laser irradiation is stronger than that collected without laser, indicating that the laser enhances the peroxidase-like activity of Cu-COF, which is attributed to the temperature increase caused by the photothermal effect.
[0076] Experimental Example 1: In vitro antibacterial performance test
[0077] Using Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) as representatives of Gram-positive and Gram-negative bacteria, the antibacterial performance of Cu-COF was detected using these two bacteria. The experiment was divided into 8 groups: I: PBS, II: Cu-COF, III: H2O2, IV: Cu-COF + H2O2, V: PBS + laser, VI: Cu-COF + laser, VII: H2O2 + laser, VIII: Cu-COF + H2O2 + laser. In the above groups, the total volume of each group of mixed solution was 1 mL, the bacterial solution concentration was 100 μL / mL (colony count was 10 8 CFU mL -1 ), the Cu-COF concentration was 125 μg / mL, the H2O2 concentration was 10 μL / mL, and the rest was made up to 1 mL with PBS. The PBS in each group was neutral. The laser group was irradiated with 638 nm infrared laser, the power density was 1.2 W / cm 2 2, and the irradiation duration was 10 min. Finally, the mixed solution of each group was placed in a shaker and incubated at 37 °C for 24 h. 80 μL of the mixed solution of each group was transferred to a solid medium (10 g LB broth + 6 g agar + 400 mL distilled water), the morphology was observed, and the colony count was calculated. And it was compared with Group I to evaluate the antibacterial effect.
[0078] As shown in Figure 7, the number of colony forming units (CFU) in the H2O2 group (III and VII) was similar to that in the PBS group (I and V) with or without laser irradiation, indicating that low concentration H2O2 (10 μL / mL) had little effect on bacterial elimination. In the Cu-COF group (II) without laser irradiation, the number of CFU was only slightly lower than that in the PBS group, indicating that the antibacterial effect of Cu-COF (125 μg / mL) alone was weak. In contrast, after laser irradiation, the number of bacterial colonies in the Cu-COF + laser group (VI) was significantly reduced, which was also demonstrated by the survival rate of Staphylococcus aureus of about 6% and the survival rate of Escherichia coli of 2.7%, which was attributed to the photodynamic synergy of the porphyrin structure. The bacterial killing effect of the Cu-COF + H2O2 group (VIII) was significantly enhanced under laser irradiation. The bacterial survival rates of Staphylococcus aureus and Escherichia coli in the Cu-COF+H2O2+laser group were 1.6% and 1.9%, respectively, indicating that Cu-COF can catalyze the decomposition of low-concentration H2O2 into toxic . OH kills bacteria, showing the great advantage of the three-in-one therapy in synergistic and effective sterilization. The combined application of Cu-COF+ H2O2+ laser has the best antibacterial effect, which is the superimposed bactericidal effect of enzyme therapy and PTT / PDT, indicating that the substance has a significant antibacterial activity.
[0079] Test Example 2: Bacterial staining test
[0080] (1) Bacterial live / dead staining
[0081] SYTO-9 and PI are used to distinguish between live and dead microbial bacteria. SYTO-9 can penetrate all bacterial membranes (intact and damaged) and mark the bacteria in green. PI can only penetrate damaged bacterial membranes, mark the bacteria in red, and reduce the green color of SYTO-9. Specifically, the experiment was divided into 5 groups: I: control (PBS); II: pure Cu-COF group; III: Cu-COF+H2O2 group; IV: Cu-COF+laser group; V: Cu-COF+ H2O2+laser group. In the above groupings, the total volume of each mixed solution was 1mL, and the bacterial solution concentration was 100 μL / mL (the number of colonies was 10 8 CFU mL -1 ), Cu-COF concentration was 125 μg / mL, H2O2 concentration was 10 μL / mL, and PBS in each group was neutral. The laser group was irradiated with 638 nm infrared laser with a power density of 1.2 W / cm 2 , the irradiation time was 10 min. Then 100 mL of bacterial solution was taken out and mixed with 20 μL SYTO-9 (1×10 -3mol / L) and 20 μL PI (1.5×10 3 mol / L) at 37°C in the dark for 15 min. After staining, the cells were centrifuged in PBS to remove excess dye. The bacteria were then resuspended in 50 μL PBS and placed on the surface of a slide. Images of E. coli and S. aureus were then captured using a fluorescent inverted microscope, with each set of experiments repeated three times.
[0082] like Figure 8 As shown in the figure, Staphylococcus aureus and Escherichia coli in the control group, Cu-COF + H2O2 group and Cu-COF group all survived, and the red fluorescence disappeared. A small amount of red fluorescence was detected in the Cu-COF + H2O2 group, and obvious red fluorescence was detected after treatment with Cu-COF + laser and Cu-COF + H2O2 + laser groups. Consistent with the results obtained by the plate count method, the bacteria treated with Cu-COF + H2O2 + laser showed the strongest red fluorescence, indicating that the number of dead bacteria increased significantly after multi-mode treatment.
[0083] (2) The morphology of bacteria under projection
[0084] Divide into 5 groups according to the method of Test Example 2 (1). Add 2.5wt% glutaraldehyde solution to each group of solutions, fix at 4℃ for 24 hours, then wash with PBS 3 times, embed and seal with agar. Treat the bacterial solution with 30%, 50%, 70%, 90%, 95% and 100% ethanol solution for 10 minutes at room temperature to dehydrate it, then dealcoholize with acetone at room temperature for 3 hours, embed with gradient infiltration, perform negative staining and slice, place the slice on a nickel grid for TEM observation and collect its morphology.
[0085] like Fig. 9 As shown, the bacterial surfaces treated with PBS and pure Cu-COF groups were smooth and intact, with Staphylococcus aureus in spherical shape and Escherichia coli in rod shape. After exposure to Cu-COF + H2O2 (Group III), only slight damage to the bacterial surface was observed, which means that the antibacterial effect of Cu-COF and H2O2 alone was minimal. However, laser irradiation of Cu-COF (Group IV) caused damage to the bacterial surface. After simultaneous treatment with H2O2 and laser (Group V), Cu-COF caused the most severe damage to the bacteria, with the collapse of the bacterial skeleton of the cells.
[0086] Test Example 3: In vitro biocompatibility test
[0087] (1) Cell hemolysis experiment
[0088] The blood used in the experiment was taken from 5-week-old female KM mice (purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.). Red blood cells (RBCs) were collected by centrifugation at 1500 rpm / min for 20 min, and then PBS buffer was added for washing. The volume ratio of the added PBS buffer to the red blood cells was about 1:1. The supernatant was removed after centrifugation, and this was repeated 4 times. The red blood cells were then mixed with PBS buffer at a volume ratio of 3:11, and the mixed red blood cells were mixed with Cu-COF (concentrations of 50, 100, 150, 200, and 250 μg / mL) at a ratio of 1:9 (v / v) and incubated at 37°C for 4 h. 100 μL of the supernatant from each tube was added to a 96-well plate, and the absorbance was measured with an enzyme reader. Distilled water was used as a positive control, and PBS was used as a negative control. The amount of hemolysis was calculated according to the following formula:
[0089] Hemolysis rate (%) = (As-An) / (Ap-An) × 100%.
[0090] Among them, "As" is the absorbance generated after adding different concentrations of Cu-COF to the red blood cell suspension. "An" represents the absorbance after adding PBS (negative control) to the red blood cell suspension. "Ap" refers to the absorbance generated by adding distilled water (positive control) to the red blood cell suspension.
[0091] like Fig.10 As shown in (a), the as-synthesized Cu-COF is blood-compatible, with no significant hemolysis in the experimental concentration range (50 to 250 μg / mL). Even at a concentration of 250 μg / mL, the hemolysis rate was only 1.37 ± 0.13%, still lower than the international safety quality standard (5%), which directly confirms the applicability of Cu-COF in blood cells.
[0092] (2) Cytotoxicity assay
[0093] In a 96-well plate, 3T3 cells (from the Cell Bank of the Chinese Academy of Sciences) were seeded at a density of 5000 cells per well, and 100 μL of cell suspension was added to each well. Three replicate wells were set up for each group. 100 μL of PBS was added to the surrounding wells to avoid excessive evaporation. After constant temperature incubation for 24 hours, 100 μL of Cu-COF suspension prepared with DMEM complete medium at different concentrations (0, 50, 100, 125, 150 and 200 μg / mL) was added to each well, followed by incubation for 72 hours, and then MTT solution (10 μl, 5 mg / mL) was added in the dark. After incubation for 4 hours, the supernatant was aspirated and 100 μL of DMSO was added to dissolve the formamide crystals formed by MTT. The 96-well plate was placed on a shaker to dissolve for 10 minutes, and the absorbance of each well at 490 nm was measured using a microplate reader. The measurement was repeated three times and the proliferation rate was calculated.
[0094] Fig.10 (b) Cell survival rate of 3T3 cells after culturing with different concentrations of Cu-COF (50-200μg / mL) for 24h, with no Cu-COF (0μg / mL) as the control group. As the concentration of the material decreases, the relative viability of the cells gradually increases. Except for the cell survival rate at a Cu-COF concentration of 200μg / mL, which was slightly lower than 85%, the survival rates of cells treated in other groups were all higher than 85%. The experimental results show that within the measured concentration range, the synthetic material has low toxicity to normal cells.
[0095] (3) Cell scratch test
[0096] 3T3 cells were seeded into 6-well plates and cultured to a density of more than 90%. The 3T3 cells in the 6-well plate were divided into two halves by gently and slowly scraping the center of the 3T3 cell monolayer with a 20 μL pipette tip. The detached cells were washed with high-pressure PBS, and then fresh DMEM basal medium containing 0, 50, 100, 125, 150 and 200 μg / mL Cu-COF was added. Finally, micrographs of 3T3 cells in each well were taken at the designated time, and each group of experiments was repeated three times.
[0097] Fig.10 (c) Cell scratch test of Cu-COF complexes with different concentrations and other control groups co-cultured with 3T3 cells. As can be seen from the figure, compared with the control group, Cu-COF in each group basically did not affect the migration ability of cells. The in vitro biocompatibility results confirmed that the Cu-COF complex has good biocompatibility and can be used as an alternative therapeutic agent for the treatment of bacterial infections.
[0098] Test Example 4: Wound healing experiment
[0099] The mice were all 5-week-old female KM mice weighing about 25g (purchased from Jinan Pengyue Experimental Animal Breeding Co., Ltd.) to establish the wound trauma model. A total of 6 groups (3 mice in each group, weighing 20-25g) were randomly selected as the blank group, and the other five groups were the control group (PBS), Cu-COF group, Cu-COF+laser group, Cu-COF+H2O2 group, and Cu-COF+laser+H2O2 group. Before the formal infection, the weight of each group of mice was weighed. Except for the blank group, the mice in other groups were anesthetized, the hair on the back was shaved, and the wound with a radius of about 5 mm was formed. Staphylococcus aureus (1×10 6CFU / mL), 24 h after infection, the mouse back wound infection model was successfully established, and the mice were divided into groups and treated according to the groups. In the above groups, the Cu-COF concentration was 125 μg / mL, the H2O2 concentration was 10 μL / mL, and the laser irradiation power was 1.2 W / cm 2 The irradiation time was 10 min. The changes in the back wounds of the mice were recorded on the 1st, 3rd, 5th, 7th, 9th and 11th days, and the weight of the mice was recorded every day. The weight changes and the back wound area of the mice were plotted. After the treatment was completed on the 11th day, blood was collected from the eyeballs of each group of mice, and the mice were killed by cervical dislocation. The skin tissue was removed, and the heart, liver, spleen, lung and kidney of the mice were removed and fixed with 4% paraformaldehyde to deform and coagulate the protein to maintain its original state. 200 μL of each blood sample was taken for routine blood analysis.
[0100] Fig.11 The wound areas of mice under different treatments were shown on days 1, 3, 5, 7, 9, and 11. On day 1, obvious redness and swelling accompanied by wound exudate were found in all groups, indicating that the construction of the animal model was successful. As the treatment time prolonged, the wounds in each group gradually healed, but the healing rates of different groups varied greatly. It can be seen that compared with the slow recovery of the wounds in the control group and the Cu-COF group, the wound repair process in the other groups was significantly accelerated, especially the Cu-COF+H2O2+laser group. On day 11, the wounds in all groups showed obvious healing, but the control group and the Cu-COF group still had a certain degree of swelling.
[0101] like Fig.12 As shown in (a), after 11 days of treatment, the wound area of mice in the Cu-COF + H2O2 + laser group was almost completely healed and much smaller than that in the other groups. Fig.12 (b) It can be seen that, similar to the blank group mice, the body weight of the mice in other groups did not change significantly during the entire treatment process, which indicates that Cu-COF has excellent biosafety.
[0102] To directly estimate the healing efficiency of infected wounds, histological analysis of newly formed skin at the wound sites of mice treated with different treatments was performed. Fig.13As shown in the figure, hematoxylin and eosin (H&E) staining and Masson staining were performed on the wound recovery after 11 days of treatment. It can be seen that the epidermal tissue of the Cu-COF+ H2O2+ laser treatment group is intact, the skin structure such as capillaries is regenerated, and there are continuous collagen fibers, which are stained blue. In contrast, the wounds treated with PBS did not generate complete epidermal tissue or collagen fibers. These results show that the Cu-COF+ H2O2+ laser treatment can significantly promote wound healing and reduce inflammation by reducing the number of bacteria.
[0103] like Fig.14 As shown, after 11 days of treatment, H&E staining was performed on the heart, liver, spleen, lung and kidney of KM mice. The results showed that there was no obvious inflammation or morphological damage in the main organs of mice in each group. These results show that Cu-COF has good biosafety in living bodies and has no obvious effect on tissues and organs.
[0104] All these results indicate that Cu-COF has good biocompatibility, potential synergistic antibacterial ability of PDT, PTT and hydroxyl radicals, and can be used as an efficient, novel and safe antibacterial agent.
[0105] Test Example 5: Degradation Test
[0106] In order to observe the degradation of Cu-COF in different environments, a Cu-COF solution with a concentration of 200 μg / mL was prepared and made up to 1 mL with PBS with pH values of 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5, respectively. The ultraviolet absorption at 650 nm was detected under an ultraviolet spectrophotometer and plotted.
[0107] like Fig.15 As shown in the figure, Cu-COF has a certain degree of degradation in different pH environments of 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5. As time goes by, the absorbance of the solution decreases significantly on the third day and the degradation situation in the pH 6.5 environment is also very optimistic, which shows that Cu-COF can achieve green degradation under mild conditions, will not cause much pollution to the environment, and is expected to develop in the direction of green and environmental protection.
[0108] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A porphyrin copper ion covalent organic framework material with excellent biocompatibility, characterized in that: The porphyrin copper ion covalent organic framework material is obtained by copolymerizing a porphyrin compound and a copper Schiff base boric acid complex by solvent thermal reaction under a protective atmosphere; The porphyrin compound is 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin; The structural formula of the copper Schiff base boric acid complex is: 。 2. The porphyrin copper ion covalent organic framework material according to claim 1, characterized in that: The preparation method of the 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin is: (1) 3,4-dimethoxybenzaldehyde and propionic acid are mixed, and then pyrrole is slowly added dropwise, and the mixture is heated for reaction. After the reaction is completed, the propionic acid is removed under reduced pressure, and the mixture is filtered and washed in sequence. A purple powder is obtained by purification by silica gel column chromatography, namely 5,10,15,20-tetrakis(3,4-dimethoxyphenyl)porphyrin; (2) Dissolve 5,10,15,20-tetrakis(3,4-dimethoxyphenyl)porphyrin in dichloromethane, then slowly add a mixed solution of boron tribromide and dichloromethane, react at low temperature, and naturally warm to room temperature after the reaction is completed. Add water to terminate the reaction, and after purification, obtain an olive green product, namely 5,10,15,20-tetrakis(3,4-dihydroxyphenyl)porphyrin.
3. The porphyrin copper ion covalent organic framework material according to claim 1, characterized in that: The copper Schiff base boric acid complex is prepared by the following method: (1) 3-Aminophenylboronic acid and methanol are mixed evenly, salicylaldehyde is added, stirred for reaction, and then filtered, washed, and dried in sequence to obtain a bright yellow product; (2) The bright yellow product obtained in step (1) is dissolved in methanol, anhydrous copper acetate is dissolved in distilled water, the two solutions are mixed and stirred for reaction, and then filtered and washed to obtain a brown-yellow product, i.e., copper Schiff base boric acid complex.
4. The porphyrin copper ion covalent organic framework material according to claim 1, characterized in that: The solvent used in the solvent thermal reaction is a mixed solution of acetonitrile, 1,4-dioxane and mesitylene; the volume ratio of the acetonitrile, 1,4-dioxane and mesitylene is 20:4:
1.
5. The porphyrin copper ion covalent organic framework material according to claim 1, characterized in that: The molar ratio of the porphyrin compound to the copper Schiff base boric acid complex is 1:
2.
6. The porphyrin copper ion covalent organic framework material according to claim 1, characterized in that: The protective atmosphere is nitrogen; the temperature of the solvent thermal reaction is 90° C. and the time is 18 h.
7. Use of the porphyrin copper ion covalent organic framework material according to any one of claims 1 to 6 in the preparation of antibacterial drugs with excellent biocompatibility or in the preparation of degradable antibacterial drugs.
Citation Information
Patent Citations
A photothermal-Fenton-like artificial nanozyme, its preparation method and application
CN115845086B
Preparation method of Meso-tetra(3,4-dihydroxy phenyl) zinc porphyrin
CN105949207A
Covalent organic framework material based on metalloporphyrin as well as preparation method and application of covalent organic framework material
CN113563551A